2018
DOI: 10.1182/bloodadvances.2018018291
|View full text |Cite
|
Sign up to set email alerts
|

Related donor transplants: has posttransplantation cyclophosphamide nullified the detrimental effect of HLA mismatch?

Abstract: We sought to identify whether posttransplantation cyclophosphamide (PT-Cy) reduces or eliminates the detrimental impact of HLA mismatching on outcomes of HLA-haploidentical related donor transplantation for acute leukemia. Data from 2143 donor-recipient pairs (n = 218 haploidentical sibling; n = 218 offspring; n = 1707 HLA-matched sibling) with acute myeloid or lymphoblastic leukemia were studied. All received a calcineurin inhibitor for graft-versus-host disease (GVHD) prophylaxis while high-dose PT-Cy was al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
38
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 24 publications
2
38
3
Order By: Relevance
“…The HAPLO group had a significantly lower incidence of cGVHD but had similar other outcomes, leading to the conclusion that a HAPLO transplantation with PTCY was a viable alternative to MSD transplantation in this patient population . Finally, in a recent joint EBMT‐CIBMTR study, patient age appeared to be important, with equivalent outcomes reported using MSDs or HAPLO donors in patients aged <55 years, but with better outcomes using MSDs in older patients …”
Section: Discussionmentioning
confidence: 94%
“…The HAPLO group had a significantly lower incidence of cGVHD but had similar other outcomes, leading to the conclusion that a HAPLO transplantation with PTCY was a viable alternative to MSD transplantation in this patient population . Finally, in a recent joint EBMT‐CIBMTR study, patient age appeared to be important, with equivalent outcomes reported using MSDs or HAPLO donors in patients aged <55 years, but with better outcomes using MSDs in older patients …”
Section: Discussionmentioning
confidence: 94%
“…In the group with patients aged 18-54 years, a comparison of haploidentical to HLA-matched sibling transplant did not reveal differences in survival. The characteristics of the patients studied in two reports and their numbers differ 1,2 and this is the most likely explanation for the differences between the two reports. As the report by Salvatore and colleagues did not consider donor-recipient relationship, we do not know whether the effect of cytogenetic risk on survival may be explained by donor-recipient relationship and patient age on survival.…”
mentioning
confidence: 77%
“…A recent joint report from the European Society for Blood and Marrow Transplant and the Center for International Blood and Marrow Transplant explored whether post-transplant cyclophosphamide can nullify the detrimental effect of HLA mismatch for acute myeloid and lymphoblastic leukemia. 2 The report showed haploidentical siblings donated to adult patients younger than 55 years and offspring donated to those 55 years and older. After adjusting for risk factors associated with survival the study concluded an HLA-matched sibling was a better choice than an offspring in patients 55 years and older.…”
mentioning
confidence: 99%
“…We sought to identify whether the influence of donor age surpasses the impact of HLA mismatching on outcomes of related donor transplantation for older acute leukaemia. As compared with two prior reports (Robinson et al ., ; Wang et al ., ), here we report our multicentre comparative evaluation of MSD versus offspring donor HCT for a homogenous group of older patients with acute leukaemia transplanted in CR1. The results of this report indicate that for patients older than 50 years, the risk of acute and chronic GVHD is comparable between groups, TRM and relapse risks were higher after MSD compared with offspring transplants.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous multicentre report under an anti‐thymocyte globulin (ATG) and granulocyte colony‐stimulating factor (G‐CSF)‐based protocol for haplo‐HCT, an offspring donor is correlated with lower TRM and higher leukaemia‐free survival (LFS) as compared with older MSD in subgroup analysis for recipients >50 years although this did not reach statistical significance (Wang et al , ). On the contrary, in a recent report from the European group for Blood and Marrow Transplantation (EBMT) and the Center for International Blood and Marrow Transplant Research (CIBMTR) on post transplant cyclophosphamide (PTCY) for haplo‐HCT, among patients aged 55–76 years, despite lower chronic GVHD incidence a higher rate of graft failure, TRM, and overall mortality were observed after transplant from offspring compared with that of MSD HCT, although there were differences in transplant platforms between the two groups (Robinson et al ., ).…”
mentioning
confidence: 97%